Towards a routing framework in ad hoc space networks. (4th December 2009) - Chen, Chao; Chen, Zesheng
A routing framework called Space Gateway Routing (SGR) is proposed for routing through Autonomous Regions (ARs) in ad hoc space networks. SGR has two integral parts: External SGR (ESGR) and Interior SGR (ISGR). ESGR addresses the delivery of different traffic types through ARs. Location-Predicted Directional Broadcast is proposed for fast delivery of remote control messages and automatic data delivery, and Receiver-Initiated On-demand Routing is for controlled data delivery. ISGR exchanges inter-AR routing information among border routers within an AR and schedules inter-AR message transmissions. Longest Queues and Minimum Waiting policies are proposed for contact allocation and inter-region message scheduling, respectively.